Aktywność obywatelska na poziomie lokalnym i jej determinanty (na przykładzie Krakowa) - Łabędź, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The text presents the civil engagement of the inhabitants of Krakow, as a place that should promote a relatively high level of engagement, against the background of the low level of civil engagement across the entire country. As a result of the analysis of some of the signs of this engagement related to the system of representation, engagement of a participative character, and engagement defined as spontaneous, it has been established however, that while there are a great deal of initiatives, the number of inhabitants participating in them does not justify the conclusion that the engagement is higher than that observed across the country. The reasons for such a state of affairs include, inter alia, the politicization of the local matters, the manner of approach on the part of the local authorities and self-government administration, but above all, a lack of interest on the part of the inhabitants, resulting from the weakness of the social capital and the existing institutional opportunities for fulfilling relevant needs. The predominant motivation with regard to taking up the engagement is a threat to one’s own interest and the predominant form is by signing petitions and appeals.
Civic engagement at the local level and its determinants (the example of Krakow)
Keywords: local civic engagement; civic participation; spontaneous civic engagement; determinants of local civic engagement